Re-invigorating Nigeria children: a consideration of right to health care and education including attendant responsibilities (2012)
Child rights have been stated in the reports of conventions, charters and conferences but the responsibilities of their implementation have not been properly articulated. Therefore, the spate of incidences of child abuse is unacceptably high. The Nigerian children continue to suffer neglect. The paper discussed concept of child and its rights. It also examined access of Nigerian child to health care and education. Also, the paper stressed the roles and responsibilities of stakeholders in ensuring the right of children to health care and education. The awareness of child’s right is better created through public enlightenment programme and the teaching of human right education in schools.